2004
DOI: 10.1111/j.1365-2753.2003.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the treatment of hypertension in diabetes mellitus: a need for better control?

Abstract: According to the WHO/ISH 1999 guidelines, approximately one out of 10 diabetic hypertensives achieved target BP control. In many instances, the drug therapy prescribed was inappropriate considering the comorbidity in patients and their laboratory findings. Improved BP control is needed in treating high-risk groups such as patients with diabetes mellitus, and efforts should be made to improve the treatment of hypertension in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
2
5
1
1
Order By: Relevance
“…Finally, it is interesting to note that the extent of BP control achieved in groups treated with mono-therapy or combination therapy did not differ significantly. Similar findings were obtained by Sequeira and co-workers and Westheim and co-workers 24,25. Potential explanation for the high proportions of poor BP control could be the lack of drug compliance among diabetic patients as a result of adverse events of the antihypertensive medications.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, it is interesting to note that the extent of BP control achieved in groups treated with mono-therapy or combination therapy did not differ significantly. Similar findings were obtained by Sequeira and co-workers and Westheim and co-workers 24,25. Potential explanation for the high proportions of poor BP control could be the lack of drug compliance among diabetic patients as a result of adverse events of the antihypertensive medications.…”
Section: Discussionsupporting
confidence: 84%
“…This is lower than for other studies, which have reported values of 40% and 38.3% for office BP control at <140/90 mm Hg and 52% for <140/80 mm Hg . However, for studies that defined stricter control targets, the percentages were much lower at 23% (<135/85 mm Hg) and 11.4% and 9.8% (<130/85 mm Hg) . It should be noted that the ABPM values used as cutoffs for the definition of BP control in the present study were not specific for patients with T2DM.…”
Section: Discussioncontrasting
confidence: 90%
“…Nowadays, there is agreement that the simple access to medical followup through provision of medical insurance has not shown satisfactory BP control in hypertensive patients [2, 3, 5, 7]. Interestingly 8.5% of patients in our primary care-based cohort were managed exclusively with nonpharmacological measures, and 75% reached a target BP < 140/90 mmHg underscoring the importance of access to ancillary services as dietary and lifestyle changes counseling (e.g., increasing physical activity) along with the medical followup.…”
Section: Discussionmentioning
confidence: 99%